Preeclampsia severa en paciente con embarazo de 41.1 semanas de edad gestacional - Bolaños Cortez, Fiama Belen (2020)
Preeclampsia is a multifactorial disorder whose main factor is idiopathic and is one of the obstetric causes of maternal and fetal death. It is characterized by increased blood pressure, the presence of proteinuria, and 1 or more signs and symptoms of systemic damage. Lack of prediction or early identification of this disorder is difficult to prevent. This clinical case study is based on a 23-year-old primigravida patient who attended the Alfredo Noboa Montenegro Hospital in Guaranda with high blood pressure, headache, epigastric pain and other symptoms and signs that denoted pre-eclampsia. In this hospital, the concurrence of patients with hypertensive disorders in pregnancy is very common due to the deficiency in prenatal controls and the high risk factors that patients present.